"Stiller Nachmittag" : Aspekte Junger Schweizer Kunst. - Stooss, Toni; Perucchi, Ursula; Schwarz, Dieter (Zürich : Kunsthaus Zürich, 1987)
Ammann, Hanspeter ; Armleder, John M. ; Cahn, Miriam ; Disler, Martin ; Etter, Olivia ; Fischli, Peter ; Geirger, Marcus ; Hahn, Alexander ; Hee, Barbara ; Himmelsbach, Rut ; Hofer, Andreas ; Huber, Felix Stephan ; Ikemura, Leiko ; Lanz, Eric ; Müller, Josef Felix ; Perrin, Carmen ; Roesch, Peter ; Ruegg, Ilona ; Rütimann, Christoph ; Schifferle, Klaudia ; Stalder, Anselm ; Villiger, Hannah ; Wanner, Franz ; Weiss, David ; Winteler, Anna
"Stiller Nachmittag" : Aspekte Junger Schweizer Kunst, Kunsthaus Zürich, 11. September bis 1. November 1987
Duits
kunstcatalogus
Keywords: Zwitserland